Modality-specific long-term memory enhancement in Heliconius butterflies - Hodge, Elizabeth A; Alcalde Anton, Amaia; Bestea, Louise; Hernández, Greta; Margereth Aguilar, Jane; Farnworth, Max S; Dalbosco Dell'Aglio, Denise; McMillan, W Owen; Montgomery, Stephen H (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2025)
How animals perceive, process and respond to environmental cues is tightly tuned to species-specific ecological demands and reflected by the structure of neural systems. In the Neotropical butterflies, , the mushroom bodies, insect learning and memory centres are significantly expanded compared with their closest relatives. This expansion coincided with the evolution of a novel diet of pollen and the ability to learn spatial foraging routes. Previous research has shown that have more accurate long-term visual memory than other Heliconiini. Here, we test whether this enhanced memory stability is specific to visual contexts by conducting a long-term olfactory memory assay in two species and two outgroup species. We found no difference in long-term olfactory memory between and outgroup Heliconiini, and combining data from olfactory and visual memory trials confirmed a modality-specific improvement in memory recall in . Tests of how Heliconiini species prioritize olfactory and visual cues when presented in conflict show no consistent pattern, suggesting that variation in memory stability is not explained by inter-specific differences in attentiveness to sensory cues. Our data provide a rare case where memory performance has been compared across species and sensory modalities to identify evidence of a modality-specific shift.This article is part of the Theo Murphy meeting issue 'Selection shapes diverse animal minds'.